Rescue of a peroxisome proliferator activated receptor gamma gene network in muscle after growth of human breast tumour xenografts - David A. Stanton; Hannah E. Wilson; Matthew G. Chapa; Jessica N. Link; Kristin Lupinacci; Werner J. Geldenhuys; Emidio E. Pistilli (Wiley, 2022)
Abstract Background Fatigue is common in patents with breast cancer (BC), and can occur in patients with early stage disease and in the absence of muscle wasting (i.e. cachexia). We have reported transcriptional and proteomic alterations in muscles from BC patients, which are associated with fatigue. Mice implanted with human BC xenografts recapitulate the muscle molecular composition changes seen in patients, coupled with a greater rate of contraction‐induced fatigue. Multiple bioinformatics platforms in both human and mouse muscles have identified peroxisome proliferator activated receptor gamma (PPARG) as central to this phenotype, with several PPARG target genes downregulated in muscle in response to tumour growth. The current study tested the hypothesis that the PPARG agonist pioglitazone (pio), a commonly prescribed diabetes drug, would rescue the transcriptional alterations observed in muscles of tumour‐bearing mice. Methods Sixteen female NSG mice were implanted with breast cancer patient‐derived orthotopic xenografts (BC‐PDOX) via transplantation of Her2/neu+ human tumour fragments. BC‐PDOX mice were randomly assigned to a treatment group that received daily oral pio at 30 mg/kg (n = 8), or a control group that received a similar volume of vehicle (n = 8). Treatment was initiated when tumours reached a volume of 600 mm3, and lasted for 2 weeks. Hindlimb muscles were isolated from BC‐PDOX and non‐tumour bearing mice for RNA‐sequencing, gene expression validation, and ATP quantification. Differentially expressed genes (DEGs) in muscles from BC‐PDOX mice relative to non‐tumour bearing controls were identified using DESeq2, and multiple bioinformatics platforms were employed to contextualize the DEGs. Results We found that the administration of pio restored the muscle gene expression patterns of BC‐PDOX mice to a profile resembling muscles of non‐tumour bearing NSG control mice. Validation of skeletal muscle gene expression by qPCR confirmed pio increased the expression of PPARG target genes (P < 0.05 in all genes but PPARG P = 0.684) in skeletal muscles. Isolated mitochondria from muscles of BC‐PDOX mice treated with pio contained greater levels of ATP (mean luminescence 33770 ± 4057 in BC‐PDOX vs. 62780 ± 11510 in BC‐PDOX PIO, P = 0.045). There were no differences in body weights (P = 0.560), muscle weights (Gas P = 0.295, Sol P = 0.365, EDL P = 0.182, TA P = 0.415) or tumour volumes (P = 0.885) in pio versus vehicle treated BC‐PDOX mice. Conclusions These data demonstrate that oral pio supplementation rescues the BC‐associated downregulation of PPARG target genes in skeletal muscle. Additionally, muscles from BC‐PDOX mice treated with pio had greater levels of ATP, which would be associated a more fatigue‐resistant muscle phenotype. Therefore, we propose that the FDA‐approved and generic diabetes drug, pio, be considered as a supportive therapy for the treatment of BC‐associated muscle fatigue.